Survey measures of inflation expectations in Poland: are they relevant from the macroeconomic perspective?. Issue 1 (2nd January 2016) - Łyziak, Tomasz
ABSTRACT: This paper estimates different versions of the stylized New Keynesian model of the Polish economy, in which alternative measures of inflation expectations are used, that is, model-consistent (rational) expectations and survey-based expectations of consumers, enterprises and financial sector analysts. To compare dynamic properties of the models, we analyse propagation of the interest rate impulse, exchange rate impulse and a permanent change of inflation target. Differences in impulse responses pose the question which model should be treated as the most adequate. Analysis of in-sample inflation forecasting errors suggests that the model with rational expectations displays the lowest forecasting accuracy, while the model using expectations of enterprises is the best-performing model. In more general terms, our analysis suggests the best way of exploiting survey data on inflation expectations is not by using them as separate forward-looking information, alternative to macroeconomic models, but by combining both types of information.